Analisis Kinerja Dokter Dalam Pengisian Rekam Medis dan Rawat Jalan Melalui Kepuasan Kerja - Muh. Abdul Aziz; Yesi Triana Sari; Alhidayatullah Alhidayatullah (Coopetition : Jurnal Ilmiah Manajemen, 2022)
Organizing medical records is a form of supporting administrative order and quality assurance in hospitals. The performance of doctors in filling RM is one of the factors in the service process at the hospital. This study aims to analyze the factors that affect the performance of doctors. This type of analytical descriptive research uses a quantitative approach with an analytical observational research design with a cross sectional design. The population in this study was 57 with a sample size of 30 samples. Technical analysis of data using univariate, bivariate and multivariate analysis with multiple regression test. The results of the research on factors that have a significant effect, namely Satisfaction with the Work Itself, Satisfaction with Salary and Satisfaction with Leadership on Doctor Performance, with a p-value of satisfaction with the work itself of 0.037 <0.05. p-value of satisfaction with salary is 0.024 <0.05 and p-value of satisfaction with leadership is 0.002. As for what does not affect satisfaction with promotions on the performance of doctors, the p-value of promotion satisfaction is 0.847.